Estudo fitoquímico e biológico dos frutos e raízes de Piper caldense C. DC. (Piperaceae) - Cavalcanti, Élida Batista Vieira Sousa (2014)
The genus Piper L. is the largest one among the Piperaceae. Containing at least 1000 species, they are located mainly on the neotropical region of Earth and it draws our attention due to its economical, cultural, chemical and medical properties, such as anti-inflamatory, antibacterial and fungicide actions. Species of the genus Piper have been becoming research sources for specific classes of secondary metabolites which play an important role concerning biological activities, including alkaloids, amides, chalcones, chromenes, flavonoids, lignans, cyclopentanediones terpenes, steroids, porphyrin derivatives and benzoic acid derivatives. Piper caldense C. DC., which is commonly known as “Pimenta d’arda”, is used in Paraíba as sedative, snake venom antidote, anti-toothache agent, and as active in located pain treatments through the use of compresses. This research reports the phytochemical study of P. caldense C. DC. fruits and roots. Through usual chromatographic methods and spectroscopic techniques such as IR, MS and one and two-dimensional 1H and 13C NMR techniques and comparison with literature data it was possible to isolate and identify a triglyceride: trilinolein, a mixture of steroids: β-sitosterol and stigmasterol and three benzoic acid derivatives: 4-hydroxy-3- ((2E, 6E, 10E) -3’, 7’, 11’, 15’-tetramethylhexadeca-2’, 6’, 10’, 14’-tetraen-1-yl) benzoic acid, 3,4-dihydroxy-2-((2Z, 6E, 10E) -3’,7’, 11’, 15’-tetramethylhexadeca-2’, 6’, 10’, 14’-tetraen-1-yl) benzoic acid e 4,5-dihydroxy-3-((2E, 6E, 10E)-11-carboxy-3’, 7’, 15’-trimethylhexadeca-2’, 6’, 10’, 14’-tetraen-1-yl) benzoic acid. The last three compounds were subjected to microbiological tests, showing antibacterial activity against Gram negative and Gram positive bacteria of clinical importance.